Directing iron transport in dicots: regulation of iron acquisition and translocation - Jeong, Jeeyon; Merkovich, Aleks; Clyne, Madeline; Connolly, Erin L (Current opinion in plant biology, 2017)
•Plants are the main source of dietary iron, yet iron uptake by plants is limited.•Iron acquisition and translocation are subject to fine-tuned homeostatic control.•New insight on molecular details of iron uptake and translocation has been revealed. Iron is essential for plant growth and development, but excess iron is cytotoxic. While iron is abundant in soil, it is often a limiting nutrient for plant growth. Consequentially, plants have evolved mechanisms to tightly regulate iron uptake, trafficking and storage. Recent work has contributed to a more comprehensive picture of iron uptake, further elucidating molecular and physiological processes that aid in solubilization of iron and modulation of the root system architecture in response to iron availability. Recent progress in understanding the regulators of the iron deficiency response and iron translocation from root to shoots, and especially to seeds are noteworthy. The molecular bases of iron sensing and signaling are gradually emerging, as well.